Stakeholder Dynamics and the Implementation of Immigration Policy: Insights from Durban Harbour - Mdakane, McCord Muziwendoda; Conradie, Hendrik Francois; Rulashe, Tando (International Journal of Qualitative Research, 2025)
Immigration control at key ports of entry, such as Durban Harbour, does not occur in isolation; it is shaped by how well government agencies communicate, coordinate, and cooperate in practice. The researchers examined the dynamics of stakeholder management and inter-agency cooperation in the implementation of immigration policies at one of South Africa’s busiest harbours. Using a qualitative case study design, in-depth interviews were conducted with senior officials from the South African Police Service (SAPS) to explore how stakeholder relationships influence policy execution. Although formal arrangements, such as Memoranda of Understanding (MoUs), Standard Operating Procedures (SOPs), and the Local Seaport Core Command (LSCC), are in place, the findings reveal persistent institutional silos, weak enforcement of collaborative frameworks, and limited accountability mechanisms. Agencies were found to prioritise internal organisational objectives over collective action, undermining the effectiveness of immigration policy enforcement. The researchers call for a national framework to strengthen inter-agency coordination and establish clearer operational roles for enhanced national security.  The research contribution lies in offering empirical insights into how cooperation, or the lack thereof, shapes immigration governance, with broader implications for public management and stakeholder theory in complex, multi-actor environments.